THE MULTIFUNCTIONALITY OF THE VILLAGE: IS THE WAY TO INNOVATIVE TRANSFORMATIONS - Ковтун, Олена (SWorldJournal, 2024)
In the face of new reforms of the Common Agricultural Policy in Europe and the emergence of new theoretical views on pluriactivity and the system of activities in the public and private spheres under a multifunctional agriculture regime, discussed in acad